Peptide selection via phage display to inhibit Leishmania-macrophage interactions - Verga, Juliane Buzzon Meneghesso; Graminha, Márcia A. S.; Jacobs-Lorena, Marcelo; Cha, Sung-Jae (Frontiers in Microbiology, 2024)
Leishmaniasis comprises a complex group of diseases caused by protozoan parasites from the Leishmania genus, presenting a significant threat to human health. Infection starts by the release into the skin of metacyclic promastigote (MP) forms of the parasite by an infected sand fly. Soon after release, the MPs enter a phagocytic host cell. We used a phage display library to identify peptides that bind to the surface of L. amazonensis (causative agent for cutaneous leishmaniasis) MPs and L. infantum (causative agent for cutaneous and visceral leishmaniasis) MPs. We found that the selected L. amazonensis binding peptide (La1) and the L. infantum binding peptide (Li1) inhibit 44 % of the internalization of parasites into THP-1 macrophage-like cells in vitro. While the inhibition of internalization promoted by La1 was specific to L. amazonensis, Li1 was effective against the internalization of both species.Importantly, we found that Li1 inhibits 84 % of L. infantum spleen and liver infection of BALB/c mice. Our findings suggest a promising path for the development of new treatments and prevention of leishmaniasis.